Factors affecting serum concentration of vancomycin in critically ill oliguric pediatric patients receiving continuous venovenous hemodiafiltration. - Bongjin Lee; Soo Jung Kim; June Dong Park; Jiun Park; Ae Hee Jung; Sun Hoi Jung; Yu Hyeon Choi; Hee Gyung Kang; Il Soo Ha; Hae Il Cheong (PLoS ONE)
Vancomycin is known to be unintentionally eliminated by continuous renal replacement therapy, and the protein bound fraction of vancomycin is also known to be different in adults and children. However, there are only a few studies investigating the relationship between the dose of continuous venovenous hemodiafiltration (CVVHDF) parameters and serum concentration of vancomycin in pediatric patients. The aim of this study was to determine clinical and demographic parameters that significantly affect serum vancomycin concentrations. This retrospective cohort study was conducted at a pediatric intensive care unit in a tertiary university children's hospital. Data from oliguric patients who underwent CVVHDF and vancomycin therapeutic drug monitoring were collected. The correlation between factors affecting serum concentration of vancomycin was analyzed using mixed effect model. A total of 177 serum samples undergoing vancomycin therapeutic drug monitoring were analyzed. The median age of study participants was 2.23 (interquartile range, 0.3-11.84) years, and 126 (71.19%) were male patients. Serum concentration of vancomycin decreased significantly as the effluent flow rate (EFR; P < 0.001), dialysate flow rate (DFR; P = 0.009), replacement fluid flow rate (RFFR; P = 0.008), the proportion of RFFR in the sum of DFR and RFFR (P = 0.025), and residual urine output increased. The adjusted R2 of the multivariate regression model was 0.874 (P < 0.001) and the equation was as follows: Vancomycin trough level (mg/L) = (0.283 × daily dose of vancomycin [mg/kg/d]) + (365.139 / EFR [mL/h/kg])-(15.842 × residual urine output [mL/h/kg]). This study demonstrated that the serum concentration of vancomycin was associated with EFR, DFR, RFFR, the proportion of RFFR, and residual urine output in oliguric pediatric patients receiving CVVHDF.